Determination and evaluation of HR-HPV genotype in different communities of Bihar, India - Parwez, Akhtar; Sunit Singh; Kumar, Rahul; Kumari, Roushan; Kumar, Vikas; Prakash, Vidyut; Ali, Mohammad (International Journal of Health Sciences, 2022)
Objective: HPV associated uteri cervix carcinoma continues to be the 2nd highest cause of death among women in India. This study aims to identify the mode of HPV transmission in different communities like Hindu, Muslim, Christian and Banjaran women of Bihar, India. Different patterns of life and cultural variations exist among Muslims, Hindus, Christians, and Banjarans. For example, Muslim wash their genital parts after urination and maintain genital hygiene, whereas Banjaran tribes, Christians, and Hindu communities do not maintain hygiene. Thus, the present study was undertaken to evaluate HR-HPV infection among healthy women. We access to genuine reason for the cause of HPV transmission in women. Methods: Ethical clearance was obtained from MCS & RC Patna, India. A total 154 urine samples have been used for detection of HR-HPV through a real time PCR technique. The DNA extraction was done from collected non-invasive urine samples. The estimation and purification of DNA purity was performed by QuantiFluor® dsDNA system and detected HPV-16 and HPV-18. Results: Overall, the prevalence of HR-HPV infection was detected to be 12.34% (19/154) whereas HPV-16 was found to be 9.9% (14/154) and HPV-18 was found to be 3.25% (5/154) in women. The lowest (2%; 1/50) prevalence of HR-HPV was observed in the Muslim community, while higher (25%, 16% and 14.71%) prevalence were found in the Banjaran, Christian and Hindu communities respectively. Conclusion: Our study indicates that personal hygiene possibly reduces HPV infection in women and the evidence suggests that male circumcision has a protective role of HPV infection in Muslim community. Therefore, personal hygiene and circumcision may reduce the risk of HPV acquisition and transmission as well as cervical cancer development in women.